Accounting Students’ Perceptions of E-Learning during the COVID-19 Pandemic - Vusi Funda; Liezel Cilliers; Daylan Staude (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
E-learning became the norm for thousands of university students in South Africa during the Covid-19 pandemic. E-learning provided opportunities to access learning material and flexible learning when students could not access classrooms. However, at traditional universities in South Africa, e-learning prior to the pandemic was limited at best, with no opportunity to provide training to lecturers on how to incorporate the technology into their teaching pedagogy once the pandemic started. This paper aims to determine the student perceptions of having to adapt to online learning in the Department of Accounting at a traditional university. A quantitative survey was used to collect data from 48 senior Accounting students during a semester course in 2019. The survey was based on the TPACK framework. The results showed that respondents indicated that their lecturers integrated digital tools in teaching and learning because social distancing and working from home demanded such practices. Overall, the students’ perceptions of e-learning were favourable, supported by their perceptions of their lecturers’ technology skills, teaching strategies, and content knowledge.